Using Eye Movements To Control A Wheelchair - Nik Hasbollah, Nik Ammar (Universiti Teknologi Petronas, 2011)
Some people in this world suffer from physical disabilities which limit their daily activities such as playing, walking, and communicating with other human beings. Many attempts have been made in order to reduce the limitations by using available resources such as the head movements, the brain activities, the eye movements and others. In this project, we will utilize the signals generated during the movements of the eyes to control a wheelchair. This attempt will help the people who suffer from the physical disability of both arms and legs thus help them to do daily activities without much supervision from other people. In the eye anatomy, two important parts are cornea and retina. Studies indicate that the metabolic rate of the cornea and the retina are different from each other, and this difference creates a very small voltage potential which is called as corneoretinal potential. The corneoretinal potential is aligned with the optical axis hence it changes with the direction of the gazes. Two pieces of electrodes will be attached on the patient's head to detect the voltage potential between these two points. An amplifier was designed to acquire the eye movement signals, and the signals patterns for each type of movements are observed. A programming code was developed based on the signals patterns to provide output controls for each type of the eye movements. The project results show that the amplifier is capable to detect the eye movements of left and right. However, some minor improvements need to be done in order to detect the upward and downward eye movements.